Do Personnel Stability, Family Business and Auditor Influence Financial Restatement? - Chen, Kai-Ling; Chang, Shen-Ho; Wang, Teng-Shih (International Journal of Economics and Financial Issues, 2016)
This paper explores how the interaction of four conditions (chief director stability, top management stability, family business and firms with big 4 auditor) results in restatements. This paper uses qualitative comparative analysis (QCA), which is a relatively new method applied in accounting research to examine the cause of the restatements systematically. The results show firms not audited by Big 4 and family business are more possible to restate the financial reports due to accounting type errors. The results also imply that non family business audited by Big 4 or family controlled firms not audited by Big4 have more chance to restate the financial reports due to material accounting errors. Last family business not audited by Big 4 has more chance to restate the financial reports voluntarily. Keywords: Personnel Stability; Qualitative Comparative Analysis; Restatement JEL Classifications: M40; M41